Relationship of Physicochemical Water Parameters and Sediment Characteristics to the Growth of Eucheuma cottonii Cultivated Using the Longline Method on Karampuang Island, West Sulawesi - Chairul Mahfud; Rahmat Januar Noor; Muhammad Aswad; Muh Ansar; Irma Yulia Madjid (Nekton, 2026)
Seaweed is an economically valuable commodity with the potential to improve the welfare of coastal communities, including Eucheuma cottonii. However, E. cottonii cultivation faces challenges from extreme changes in aquatic conditions and sediment input from river estuaries, which may inhibit its growth. This study aimed to analyze the relationship between physicochemical water parameters and sediment characteristics and the growth of E. cottonii cultivated using the longline method on Karampuang Island, West Sulawesi. A quantitative approach was applied through a field experiment using a completely randomized design (CRD) on three longline stretches over 30 days. Water quality and sediment parameters were analyzed descriptively, while relationships among variables were tested using partial correlation analysis. The results showed that most physicochemical water parameters were within the optimal range, except for current velocity, which was relatively low at 0.11 m/s. Sediment at the study site was dominated by medium sand, with a dynamic daily sedimentation rate ranging from 0.08 to 0.43 g/L/hour. The absolute growth of E. cottonii reached 477.00 g, with an average daily growth rate of 16.66 g/day. Partial correlation analysis showed that the growth of E. cottonii was closely associated with sedimentation rate and salinity. The cultivation of E. cottonii using the longline method on Karampuang Island showed positive growth, supported by suitable physicochemical water conditions, although sedimentation remained dynamic.